A Simple Method for Exposing Repository Content on Institutional Websites - Villarreal, Gonzalo Luján (2017)
This article presents the development of an OpenSearch client to retrieve content from OpenSearch-compliant digital repositories, using this client as part of CMS modules, namely Wordpress, Joomla and Choique –which are widely used in the Universidad Nacional de La Plata (UNLP) and in the Comisión de Investigaciones Científicas (CIC) (Argentina). An institutional web visibility project is also introduced to create websites for research and development units (centers, laboratories and institutes), and link them to institutional repositories through these developments. This work highlights the importance of collaborating with R&D units to improve their exposure of research lines, projects and activities on the Web, as well as to size the opportunity offered by a service of this type to leverage and promote the use of institutional repositories. The ultimate goal is to increase visibility for the UNLP’s production, bearing in mind that it can be found in different channels and platforms.